Screening of local barley accessions for sensitivity to photoperiod - I. A. Zveynek; O. N. Kovaleva (Труды по прикладной ботанике, генетике и селекции)
Background. Earliness of barley is an important trait for increasing the yield of this crop, especially in regions where abiotic factors are determinant. This work is dedicated to the identification of the eam8 gene in local barley accessions from the VIR collection. It would be possible to find sources of weak sensitivity to photoperiod to be used in breeding practice.Materials and methods. In Pushkin and Pavlovsk Laboratories of the N. I. Vavilov All-Russian Institute of Plant Genetic Resources (VIR, St. Petersburg), 1460 local barley accessions from 26 countries with a short photoperiod of vegetation were studied. These countries are included in five centers of barley diversity: the Abyssinian, the Near East, the Mediterranean, the Central Asian, and the New World. The experiments were performed in the THERMO 818 (3751) climate chamber. Barley seeds were planted in cuvettes with moistened cotton wool. After the emergence of shoots, they were placed in the climate chamber where the plants remained until the stage of the second leaf with the 10-hour photoperiod and the temperature regime of a low daytime (+8°C) and high nighttime (+25°C) temperatures. Yellow color of a plantlet was the marker for the expression of the eam8 gene. Two varieties were used as references: 'Mari Svalofs' (k-19354; var. nutans Schubl.; Genotype eam8eam8) insensitive to photoperiod, and 'Belogorsky' (k-22089; var. pallidum Ser., var. ricotense Regel; Genotype Eam8Eam8) responding to a short day.Results and conclusions. Phenotypic screening of barley samples from 26 countries with a short photoperiod resulted in identification of 1379 forms with the Eam8Eam8 genotype (sensitive to a short day), 44 accessions with the eam8eam8 genotype (insensitive to a short photoperiod), and 37 heterogeneous accessions. Local barleys from Dagestan demonstrated the highest occurrence of forms with the eam8 gene (15.9%). The Near East and Central Asian centers of barley diversity were notable for the occurrence of local accessions with the recessive allele of the Eam8 gene. Accessions with the eam8eam8 genotype and heterogeneous forms can serve as sources of earliness in regions with short-light days. In order to include such sources in commercial barley cultivar breeding programs, they should be searched for in countries with a mountainous landscape and a short photoperiod.